2005
DOI: 10.1097/00003446-200506000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Auditory-Visual Speech Perception and Auditory-Visual Enhancement in Normal-Hearing Younger and Older Adults

Abstract: Overall, the findings suggest that the poorer performance of older adults in the AV condition was a result of reduced speechreading abilities rather than a consequence of impaired integration capacities. The pattern of correlations across the three stimulus types indicates some overlap in the mechanisms mediating AV perception of words and sentences and that these mechanisms are largely independent from those used for AV perception of consonants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
291
3
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(330 citation statements)
references
References 24 publications
34
291
3
2
Order By: Relevance
“…One potential shortcoming of previous in measuring integration relates to the inherent difficulty of defining what is meant by "integration." For instance, integration has been operationally defined as susceptibility to the McGurk effect (Grant, 2002), audiovisual enhancement in accuracy scores (Bergeson & Pisoni, 2004;Sommers et al, 2005;Sumby & Pollack, 1954), superadditivity in the neural signal (Calvert & Campbell, 2003;Calvert, Campbell, & Brammer, 2000), the combining of the intermodality information (as in FLMP; Massaro, 2004), or the difference between obtained accuracy scores compared to model predictions derived from confusion matrices (Grant, 2002;Grant et al 1998). A promising course of action has been to formalize these definitions and use them to test models against one another (e.g., Grant et al, 1998;Massaro, 1987aMassaro, , 1998.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One potential shortcoming of previous in measuring integration relates to the inherent difficulty of defining what is meant by "integration." For instance, integration has been operationally defined as susceptibility to the McGurk effect (Grant, 2002), audiovisual enhancement in accuracy scores (Bergeson & Pisoni, 2004;Sommers et al, 2005;Sumby & Pollack, 1954), superadditivity in the neural signal (Calvert & Campbell, 2003;Calvert, Campbell, & Brammer, 2000), the combining of the intermodality information (as in FLMP; Massaro, 2004), or the difference between obtained accuracy scores compared to model predictions derived from confusion matrices (Grant, 2002;Grant et al 1998). A promising course of action has been to formalize these definitions and use them to test models against one another (e.g., Grant et al, 1998;Massaro, 1987aMassaro, , 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it is possible that different listeners will use differing strategies. Such variation may depend on hearing ability, cognitive status, and susceptibility to the McGurk effect; all of which are known to influence multisensory integration abilities (e.g., Altieri & Hudock, 2014;Erber, 2003;Sommers, Tye-Murray, & Spehar, 2005).…”
Section: Measures Of Capacity and Relative Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Picou et al (2011) found that the person with low WMC did not derive any benefit from the presence of visual cues whereas person with high WMC did derive benefit from the presence of visual cues in cued recall of words. Sommers, Tye-Murray and Spehar (2005) found that the AV integration for speech perception in noise was similar across young and older adults with normal hearing, but the young adults had better speech reading skills compared to older adults and hence had better performance in the AV modality.…”
Section: Visual Cuesmentioning
confidence: 90%
“…HL results primarily in a decline in auditory speech perception (Humes & Roberts 1990); however, changes in visual perceptual abilities indicate that adaptation to HL is not limited to the auditory modality. On the one hand, younger adults with early-onset hearing impairment are better at lipreading sentences than controls (Auer et al 2007), but even in normal-hearing (NH) people, this ability declines with age (Cienkowski & Carney 2002;Hay-McCutcheon et al 2005;Sommers et al 2005). Although investigations of unimodal perception in isolation help us understand how HL in older adults affects auditory and visual abilities, everyday perception for most people involves the combination of these inputs.…”
Section: Introductionmentioning
confidence: 99%